Camel milk exosomes regulate glucose metabolism by inhibiting mitochondrial complex I in hepatocytes - Bin Yang; Shifeng Du; Ling Liu; Jingjing Wang; Demtu Er (BMC Veterinary Research, 2025)
Abstract Background Camel milk is known to have hypoglycemic properties. Previous studies found that camel milk exosomes (CM-exo) may regulate cellular glucose metabolism through the inhibition of mitochondrial complex I, but this hypothesis has not been verified by other experiments. The objective of this study was to verify the hypothesis that CM-exo regulated glucose metabolism in hepatocytes by inhibiting mitochondrial complex I pathway. AML12 cells were treated with extracted exosomes from camel milk and the effect of the CM-exo on cell viability was examined by cell counting kit (CCK)-8 assays. The glucose content of the cell culture medium was measured to determine the glucose consumption of the cells. Lactate release from the cells was determined by measuring the lactate content in the cell culture medium. The glycogen content of AML12 cells was detected. The activity of complex I and the contents of ATP, NAD+ and NADH were measured. The protein expression levels of adenosine monophosphate-activated protein kinase (AMPK) and phosphorylated AMPK (p-AMPK) were detected by western blotting. The AML12 cells were treated with medium containing CM-exo and gluconeogenic substrates and the glucose content in the cells was determined. The protein expression levels of ten-eleven translocation methylcytosine dioxygenases (TET3), hepatocyte nuclear factor 4α-Promoter 2 (HNF4α-P2), phosphoenolpyruvate carboxykinase (PEPCK), glucose-6-phosphatase (G6PC), glycogen synthase kinase 3β (GSK3β) and phosphorylation of GSK3β (p-GSK3β) were detected by western blotting. Results The results of this study showed that a high dose of CM-exo inhibited the viability of AML12 cells. It promoted glucose consumption, glycogen content and lactate release in AML12 cells, inhibited complex I activity, ATP content, NAD+ content, and NAD+/NADH ratio, and increased NADH content. The CM-exo increased the protein levels of p-AMPK, p-GSK3β, the protein expression ratio of p-AMPK/AMPK, p-GSK3β/GSK3β and decreased the glucose content and the protein expression levels of intracellular TET3, HNF4α-P2, PEPCK and G6PC. Conclusions By inhibiting the activity of mitochondrial complex I in hepatocytes, CM-exo inhibited oxidative phosphorylation, oxidation of NADH to NAD+ and synthesis of ATP, enhanced glycolysis, activated AMPK and resulted in decreased gluconeogenesis and increased glycogen synthesis.